Correlation between Inflammatory Marker and Glycemic Control in Patients with Ischemic Heart Disease (Bangladesh Heart Journal, 2018)
Background: Recent evidence suggests that inflammatory markers and poor glycemic control are significantly associated with the development of cardiovascular complications. The purpose of this study was to determine the association between inflammatory marker (CRP) and glycemic status (HbA1c) in ischemic heart disease patients.Method: This cross sectional study was performed on 668 patients of ischemic heart disease in the Department of Cardiology, Dhaka Medical College Hospital, Dhaka, who underwent Coronary angiogram from January 2017 to December 2017. CRP value were divided into normal (10 mg/L) and HbA1c was divided